The Possibility Of Tax Avoidance Perspective Of Company Ownership And The Risk Of Loss - Rizal, Muhammad (Perhimpunan Sarjana Ekonomi dan Bisnis, 2022)
The amount of taxes paid by companies to the state is one of the triggers for avoidance behavior, and psychologically this is a natural response, because taxes are seen as a reduction in wealth/welfare. Therefore, various other negative conditions are very likely to be triggers for tax avoidance behavior, for example experiencing losses and voting for companies. Based on these conditions, this research was conducted to examine the possibility of causation between corporate tax avoidance behavior and the risk of loss and company ownership. To answer this goal, the positivism method was determined as a research fundamental. The research object is a manufacturing company in Indonesia, and the research sample is financial reports for 5 years, totaling 100 data. Data is secondary, taken purposively. To reveal the research phenomenon, the data analysis used multiple linear regression techniques, which consisted of hypothesis testing and terminals. The results of the study suggest that there is a tendency for companies to avoid taxes in difficult financial conditions. In addition, it is also possible that ownership of the company can be a trigger for the company to avoid taxes, because it directly feels reduced profits.